Cooperative control for multiple interceptors to maximize collateral damage - Lee, Chang-Hun; Tsourdos, Antonios (Elsevier, 2019)
In this paper, a cooperative control method to satisfy the relative interception angle constraints in multi-to-one engagement case is proposed. In this study, we consider the relative interception angle constraints of the multiple interceptors, which is intended to enhance the survivability of the multiple interceptors against a defense system of high value target as well as to maximize the collateral target damage. The proposed cooperation control can reduce the total control energy required while satisfying the given interception angle constraints. This characteristic allows to increase the change of mission in the multi-to-on engagement scenario. In this paper, the numerical simulations are conducted to verify the feasibility of proposed concept.
Keywords: Cooperative control; multiple interceptors; network system; interception angle control; collateral damage